Tihany '99 : international art camp. - Istvan, Eross; MissionArt Gallery Budapest (Tulsó p'art, 1999)
Borgó ; France, John ; Ignatescu, Anca ; József, Tasnádi ; Achimescu, Bogdan ; Csaba, Balogh ; Cartier, Valérie ; Istvan, Eross ; Kloos, Luise ; Beumer, Astrid ; Keijser, Hester ; Beierle, Norman ; Chen, Shang-pin ; Liu, Po-Chun ; László, Zoltán
Geboortedatum en adres
Engels & Hongaars
Tihany '99 : International art camp, MissionArt Gallery Budapest, 11.03 - 10.04.2000 / The Art Camp took place at the Tihany Art Vilage of the Hungarian Fine Arts Academy between 24.09 - 10.10.2000
kunstcatalogus